Landslide-inventory of the Cinque Terre National Park (Italy) and quantitative interaction with the trail network. Issue 2 (3rd July 2019) - Raso, Emanuele; Cevasco, Andrea; Di Martire, Diego; Pepe, Giacomo; Scarpellini, Patrizio; Calcaterra, Domenico; Firpo, Marco
ABSTRACT: The Cinque Terre National Park (38 km 2 ) has recently recorded a remarkable increase in tourists involved in outdoor activities such as hiking. However, due to the actual slope degradation issues that affect this outstanding terraced landscape, hiking trails are increasingly threatened by the impact of landslides. This produces severe landslide-related risk scenarios for hikers. In this study, a landslide inventory map (at 1:45000 scale) has been prepared through the revision/update of previous database and the analysis of air-photos and satellite images coupled with field surveys. Furthermore, a quantitative evaluation of the interaction between landslides and hiking trails has been performed by the definition of a Footpath Landslide Index. More than 400 landslides were identified highlighting that these phenomena represent the main source of hazard. The findings of this study reveal that side-hill trails are the most hazardous since hikers can be potentially affected by flow-like or fast-moving landslides.